Analisis Bibliometrik Penelitian Asbabul Wurud pada Database Dimensions - Ghina Mutmainnah; Busro Busro (Gunung Djati Conference Series, 2023)
Asbabul wurud-related works are still being developed and published in a variety of scholarly discourses. This study aims to discuss the keyword "Asbabul Wurud" in database dimensions using bibliometric techniques. The method in this study uses bibliometric analysis using data from international publications sourced from database dimensions. Data collection through searches with the keywords "Asbabul Wurud". In this study, there are five processes that are completed: choosing keywords, data search, choosing articles for data validation, and data analysis. In the research category, asbabul wurud is mainly studied in the fields of philosophy and religious studies. The development trend of asbabul wurud research tends to increase every year with most of the research in 2020. There is no dominant researcher and the number of publications is evenly distributed, namely no more than 4 publications, such as Eko Nopriyansa. Asbabul Wurud's research publishers are dominated by journals in the fields of theology and Islamic studies, namely the Living Hadith Journal. This research is useful for knowing the development of asbabul wurud studies related to program coordination.